Assessment of pollutant level and forecasting water pollution of Chennai coastal, TamilNadu using R - Padmanaban, Rajchandar (2018)
Padmanaban, R., Karuppasamy, S., & Narayanan, R. (2018). Assessment of pollutant level and forecasting water pollution of Chennai coastal, TamilNadu using R. Indian Journal of Geo-Marine Sciences, 47(7), 1420-1429.